2002
DOI: 10.1046/j.1440-1843.2002.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values for cardiopulmonary exercise testing in sedentary Chinese adults

Abstract: Previously established prediction equations for maximal exercise performance during CPET based on non-Chinese populations may not be applicable to Chinese subjects in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
(40 reference statements)
2
25
0
2
Order By: Relevance
“…We believe that VO 2 values vary depending on the population studied as we can see in the Brazilian study by Neder et al 24 and the Chinese study by Ong 22 , who found lower values when compared with European and North American studies.…”
Section: Herdy and Uhlendorf Reference Values For The Cardiopulmonary Ementioning
confidence: 83%
“…We believe that VO 2 values vary depending on the population studied as we can see in the Brazilian study by Neder et al 24 and the Chinese study by Ong 22 , who found lower values when compared with European and North American studies.…”
Section: Herdy and Uhlendorf Reference Values For The Cardiopulmonary Ementioning
confidence: 83%
“…Recently, well-designed studies that measured CRF directly using the treadmill test have been published for relatively large populations, especially for Westerners [12][13][14]. Although there have been attempts to present age-related mean reference values for Asian populations [24,[27][28][29], these studies also had small sample sizes and/or used cycle ergometers instead of the treadmill test.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first study to investigate the reference values of CRF using the treadmill test for Asians with a large sample size and high quality. Although the study was confined to Koreans, it was meaningful because it was aimed at a relatively large population group as compared with the previous studies of Asian populations [24,[27][28][29]. Another advantage of this study was that the percentage of predicted exercise capacity of Koreans by sex and age can be easily ascertained through the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of exercise, the reasons for termination, as well as the Borg dyspnoea score [14], were obtained from the subjects. The predicted V9O 2 ,max was derived from regressions based on age, sex, weight and height from published data obtained from the local population [15].…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%